Transitive regret - Sushil Bikhchandani; Uzi Segal (Theoretical Economics, 2011)
Preferences may arise from regret, i.e., from comparisons with alternatives forgone by the decision maker. We ask whether regret-based behavior is consistent with non-expected utility theories of transitive choice and show that the answer is no. If choices are governed by ex ante regret and rejoicing then non-expected utility preferences must be intransitive.
Keywords: D81; 330; Regret; transitivity; non-expected utility